The Nature of Justice in Constitutional Philosophy - Yunus, Nur Rohim (ADALAH, 2023)
This essay discusses the nature of justice in constitutional philosophy as an effort to achieve a balance between individual rights and collective interests. Justice is not a static concept, but continues to evolve along with social and political changes. This essay explains several strategic steps to uphold constitutional justice, including equitable legal reform, strengthening judicial institutions, increasing access to justice, and implementing a multidisciplinary approach in public policy. The state can create a more inclusive and bias-free legal system by understanding justice from a philosophical, sociological, and legal perspective. The active involvement of various stakeholders is key to realising real justice. Thus, this essay emphasises that justice must be realised in normative concepts and sustainable policy practices.